Congenital laryngeal cyst causing respiratory distress in a neonate: a rare case report - Basak, Aniruddha; Dey, Debaleena (International Journal of Contemporary Pediatrics, 2021)
Congenital laryngeal cyst is a rare but responsible of upper airway obstruction which can be potentially life-threatening. The most common symptoms are inspiratory stridor, dyspnea, cyanosis, abnormal voice and difficulty with feeding. It should be differentiated from laryngomalacia. It is diagnosed by flexible fibro-optic laryngoscopy. Surgical options are endoscopic excision, needle aspiration, de-roofing, external laryngo-fissure and lateral pharyngotomy. The best treatment consists in the entire removal of the cyst. This case report described the case of 28 days old neonate with a severe airway distress and stridor caused by a congenital laryngeal cyst which has been managed by de-roofing of the cyst entirely with flexible laryngoscope.